2020
DOI: 10.3390/ijerph17093170
|View full text |Cite
|
Sign up to set email alerts
|

How Are Information and Communication Technologies Supporting Routine Outcome Monitoring and Measurement-Based Care in Psychotherapy? A Systematic Review

Abstract: Psychotherapy has proven to be effective for a wide range of mental health problems. However, not all patients respond to the treatment as expected (not-on-track patients). Routine outcome monitoring (ROM) and measurement-based care (MBC), which consist of monitoring patients between appointments and using this data to guide the intervention, have been shown to be particularly useful for these not-on-track patients. Traditionally, though, ROM and MBC have been challenging, due to the difficulties associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…While developing alternatives to face-to-face multidimensional treatments for chronic pain is indeed important, most patients still advocate individual, face-to-face treatments [ 67 ] and the first-line intervention for patients with chronic pain, namely medical treatment, will probably continue to require some patient-professional face-to-face interaction. Thus, the development of tools that improve face-to-face interventions and allow for a rapid adaptation of treatments as a function of patient evolution during treatment, as in measurement-based care [ 68 ], should be a major focus of research in chronic pain settings. This study may provide some novel insights about the potential utility, as well as the implementation challenges of this new approach to monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…While developing alternatives to face-to-face multidimensional treatments for chronic pain is indeed important, most patients still advocate individual, face-to-face treatments [ 67 ] and the first-line intervention for patients with chronic pain, namely medical treatment, will probably continue to require some patient-professional face-to-face interaction. Thus, the development of tools that improve face-to-face interventions and allow for a rapid adaptation of treatments as a function of patient evolution during treatment, as in measurement-based care [ 68 ], should be a major focus of research in chronic pain settings. This study may provide some novel insights about the potential utility, as well as the implementation challenges of this new approach to monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methodologists have recommended "factorial designs" to test the active components of complex therapies. 64 These factorial designs permit to explore main effects of components and interactions among components. In short, using our multicomponent treatment as example, patients would be As stated above, this is the first study to demonstrate the effectiveness of a multicomponent treatment that specifically integrates PNE in patients with FM.…”
Section: Discussionmentioning
confidence: 99%
“…In short, using our multicomponent treatment as example, patients would be As stated above, this is the first study to demonstrate the effectiveness of a multicomponent treatment that specifically integrates PNE in patients with FM. There are many studies that support the individual effectiveness of each of the treatment components that constitute this multicomponent therapy 11,[13][14][15][18][19][20][21][22][23][24][25][26][27][63][64][65][66][67][68][69][70][71][72] . In spite of the complexity of integrating different ingredients, the present RCT was designed on the basis of a clear and replicable methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that certain personality characteristics (e.g., high neuroticism) may be a risk factor to pregnant women’s wellbeing deterioration and therefore should be assessed early during pregnancy mental health screening, which might be facilitated through the use of ICT tools. In a related topic, Gual-Montolio et al [ 13 ] presented a systematic review about the use of ICTs for routine outcome monitoring (ROM) and measurement-based care (MBC) in face-to-face psychological interventions for mental health problems. The eighteen articles revised showed that handheld technologies such as smartphone apps, tablets, or laptops were used for assessment and feedback during psychological interventions (including ROM and MBC), providing evidence about their feasibility and acceptability.…”
mentioning
confidence: 99%